2016
DOI: 10.1016/j.jinorgbio.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal norharmane compounds as possible cytotoxic agents: New insights based on a coordination chemistry perspective

Abstract: New first-row transition-metal compounds with the ligand norharmane (9H-Pyrido[3,4-b]indole; Hnor) are reported. The compounds have the general formula [M(LL)(Hnor)(NO)](MeOH) (M=Co, Ni, Cu, Zn; LL=2,2'-bipyridyl (bpy), 1,10-phenanthroline (phen)) and have been characterized by physical and analytical methods. X-ray structural analysis revealed that the compound of formula [Cu(phen)(Hnor)(NO)], (1) has a distorted 6-coordinated octahedrally-based geometry, with a planar-based [CuNO] core, where Cu-L varies bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…They exhibited strong charge-transfer bands near 335 and 355 nm, respectively and 1 displayed a d-d transition ~ 645 nm in DMSO (see SI for Figure S1 and S2 ). Further, 1 and 2 are considerably stable toward air and moisture for>24 h. The structures of 1 and 2 exhibited distorted square pyramidal geometry, which is similar to what the literature reported previously ( Khan et al, 2016 ) and the analytical data are found to be consistent with the proposed molecular formulae (Scheme in Fig. 1 ) .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…They exhibited strong charge-transfer bands near 335 and 355 nm, respectively and 1 displayed a d-d transition ~ 645 nm in DMSO (see SI for Figure S1 and S2 ). Further, 1 and 2 are considerably stable toward air and moisture for>24 h. The structures of 1 and 2 exhibited distorted square pyramidal geometry, which is similar to what the literature reported previously ( Khan et al, 2016 ) and the analytical data are found to be consistent with the proposed molecular formulae (Scheme in Fig. 1 ) .…”
Section: Resultssupporting
confidence: 87%
“…The FT-IR spectra of 1 and 2 exhibited N-H bands at ~ 3400 cm −1 for the Hnor ligands. ( Calligaris and Carugo, 1996 ) described characteristics of tryp’s coordinated NH 2 bands around 3290 cm −1 and carboxylate (-O-C = O) bands ~ 1625 cm −1 , which showed a significant shift from the free tryp ~ 1660 cm −1 ( Khan et al, 2016 ). The anti-symmetric and symmetric -C = O stretching vibration shifted to lower frequencies that confirms the terminal coordination mode of carboxylate.…”
Section: Resultsmentioning
confidence: 99%
“…Also, these complexes were cytotoxic against different cell lines. [45][46] Recently, it was demonstrated that silver(I) complexes of nHo were light stable and also cytotoxic against different cell lines 47 . Moreover, the complexes used in this work were cytotoxic against A549 cells, 37 phototoxic against S. typhimurium and showed photosensitizing potential against plasmid DNA 48 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The cytotoxicity of the molecules was analyzed with the help of an MTT assay following standard protocol [ 49 ] reported earlier by us. [ 50–54 ] Following, in brief, it has been described in the SI.…”
Section: Methodsmentioning
confidence: 99%